Metabolomics and Transcriptomics in Legumes Under Phosphate Deficiency in Relation to Nitrogen Fixation by Root Nodules - Abdelrahman, Mostafa; El-Sayed, Magdi A.; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Alqarawi, Abdulaziz A.; Burritt, David J.; Tran, Lam-Son Phan (Frontiers in Plant Science, 2018)
Phosphate (Pi) deficiency is a critical environmental constraint that affects the growth and development of several legume crops that are usually cultivated in semi-arid regions and marginal areas. Pi deficiency is known to be a significant limitation for symbiotic nitrogen (N2) fixation (SNF), and variability in SNF is strongly interlinked with the concentrations of Pi in the nodules. To deal with Pi deficiency, plants trigger various adaptive responses, including the induction and secretion of acid phosphatases, maintenance of Pi homeostasis in nodules and other organs, and improvement of oxygen (O2) consumption per unit of nodule mass. These molecular and physiological responses can be observed in terms of changes in growth, photosynthesis and respiration. In this mini review, we provide a brief introduction to the problem of Pi deficiency in legume crops. We then summarize the current understanding of how Pi deficiency is regulated in legumes by changes in the transcriptomes and metabolomes found in different plant organs. Finally, we will provide perspectives on future directions for research in this field.